Effect of herbicides for the control of Fimbristylis miliacea (L.) Vahl. in rice. - Begum, Mahfuza; Juraimi, Abdul Shukor; Syed Rastan, Syed Omar; Amarthalingam, Rajan; M., Azmi (Asian Network for Scientific Information, 2008)
The experiment was conducted in the glasshouse at Universiti Putra Malaysia to determine the efficacy of herbicides with different modes of action against a Fimbristylis miliacea population and increased rice yield potentiality. Nine early post emergence herbicide treatments such as bensulfuron, cinosulfuron, pyrazosulfuron, cinosulfuron+pretilachlor+safener, 2, 4-D (amine), pretilachlor+safener, bentazone, fentrazamide+propanil and bispyribac-sodium were applied singly or in mixtures. A weed-free (hand-weeded) treatment and an unweeded treatment served as controls. The treatments were arranged in a randomized complete block design with four replications. A weed-free (hand-weeded) treatment and an unweeded treatment served as controls. The treatments were arranged in a randomized complete block design with four replications. Data on crop phytotoxicity, weed control, chlorophyll content, plant height, productive tillers, total tillers, panicle length, grains per panicle, 1000 grain weight, % filled grains per panicle, grain yield and straw biomass were recorded to evaluate efficacy of the different treatments. All tested herbicides were effective in controlling F. miliacea, but the herbicides bensulfuron and fentrazamide+propanil increased grain yield by more than 80% compared to the unweeded treatment and were comparable to the weed-free treatment.